Pemilihan Strategi Pembelajaran Maharah Qirā’ah Berdasarkan Tingkatan Pelajar Bahasa Arab - Alma Idatun Nahlah (Yayasan Mutiara Hati Moeslem, 2025)
This study aims to examine various learning strategies for reading comprehension (maharah qirā’ah) that are appropriate for the levels of Arabic language learners: beginner, intermediate, and advanced. This study uses a descriptive qualitative approach through literature review. The results of the study indicate that at the beginner level, strategies such as drills, phonics, and audio-visual media are effective in building a reading foundation. At the intermediate level, task-based strategies, reading comprehension, and paired reading can improve fluency and comprehension of texts. Meanwhile, at the advanced level, close reading, critical text analysis, and the integration of interactive technology have proven effective in understanding complex texts. This article is expected to be a reference for Arabic language educators in designing effective learning strategies, appropriate to students' ability levels, and able to increase learning motivation, as well as provide a basis for further research in the development of media and learning methods for reading comprehension (maharah qirā’ah).